Vermifiltration and sustainable agriculture: unveiling the soil health-boosting potential of liquid waste vermicompost - Malal, Halima; Romero, Veronica Suarez; Horwath, William R.; Dore, Sabina; Beckett, Patrick; Ait Hamza, Mohamed; Lakhtar, Hicham; Lazcano, Cristina (Frontiers in Sustainable Food Systems, 2024)
Vermifiltration is a promising technique that can help recover nutrients from wastewater for further use in agriculture. We conducted a field experiment to assess the effectiveness of vermicompost produced from the vermifiltration of liquid waste (manure and food production waste) and how it can affect the soil health and yield of a squash crop. We tested the effect of three rates of vermicompost (low, medium, and high) applied over two consecutive years and measured physical, chemical, and biological soil health indicators, squash yield, and nutritional status. The results showed that the use of vermicompost, especially at a high rate, increased total soil carbon, total nitrogen, potentially mineralizable nitrogen, and particulate organic matter, as well as the activity of C-N-P cycling enzymes, as compared to a control with only inorganic fertilization. The yield of the squash crop remained stable, while the crop nutritional value improved as the levels of boron and copper in the treated squash increased. These findings indicate an improvement in soil health after the use of vermicompost. Overall, results strongly support using this type of vermicompost as a sustainable management approach to recycle nutrients and enhance soil health.